A general spectral difference method for calculating the minimum safety distance to avoid the pounding of adjacent structures during earthquakes. (1st November 2017) - Yu, Zhi-wu; Liu, Han-yun; Guo, Wei; Liu, Qun
Highlights: Proposed a new method (gSDM) to calculating minimum safety distance between adjacent buildings. The gSDM is based on the pseudo-excitation method. The gSDM can consider any complex non-proportional damping case. The gSDM has solid theoretical basis because of abandoning the force decoupling assumption. Comparison with cSDM and SRSS, the gSDM has a higher precision result. Abstract: With the development of cities, buildings have become increasingly concentrated. Therefore, there are serious potential collision dangers between the adjacent buildings or the building partitions under earthquakes, hence buildings need to set the appropriate safety distance to avoid pounding. However, the calculation of the minimum safety distances (MSD ) of the adjacent buildings in Chinese Code is rough and arbitrary, while the traditional response spectrum method is derived based on the assumption of proportional damping and it is difficult to consider the non-proportional damping characteristics for large and complex building systems. Based on the above, this paper proposes a new general spectral difference method (gSDM) to calculate the MSD. First, the pseudo-excitation method is used to derive the relative displacement random expression of adjacent buildings during earthquakes. Then, combined with the response spectrum method, the gSDM formula is established, in addition, the explicit expressions of combination coefficient in the gSDM formula are given. Finally, the examples of two adjacent multi-storey shear-buildings are used to illustrate the accuracy and wide adaptability of the gSDM during the El-Centro earthquake. The results compared and discussed in detail with the classical spectral difference method (cSDM ), SRSS method and time history analysis.